Modeling the human Nav1.5 sodium channel: structural and mechanistic insights of ion permeation and drug blockade - Ahmed M; Jalily Hasani H; Ganesan A; Houghton M; Barakat K (Dove Medical Press, 2017)
Marawan Ahmed,1 Horia Jalily Hasani,1,* Aravindhan Ganesan,1,* Michael Houghton,2–4 Khaled Barakat1–3 1Faculty of Pharmacy and Pharmaceutical Sciences, 2Li Ka Shing Institute of Virology, 3Li Ka Shing Applied Virology Institute, 4Department of Medical Microbiology and Immunology, Katz Centre for Health Research, University of Alberta, Edmonton, AB, Canada *These authors contributed equally to this work Abstract: Abnormalities in the human Nav1.5 (hNav1.5) voltage-gated sodium ion channel (VGSC) are associated with a wide range of cardiac problems and diseases in humans. Current structural models of hNav1.5 are still far from complete and, consequently, their ability to study atomistic interactions of this channel is very limited. Here, we report a comprehensive atomistic model of the hNav1.5 ion channel, constructed using homology modeling technique and refined through long molecular dynamics simulations (680 ns) in the lipid membrane bilayer. Our model was comprehensively validated by using reported mutagenesis data, comparisons with previous models, and binding to a panel of known hNav1.5 blockers. The relatively long classical MD simulation was sufficient to observe a natural sodium permeation event across the channel’s selectivity filters to reach the channel’s central cavity, together with the identification of a unique role of the lysine residue. Electrostatic potential calculations revealed the existence of two potential binding sites for the sodium ion at the outer selectivity filters. To obtain further mechanistic insight into the permeation event from the central cavity to the intracellular region of the channel, we further employed “state-of-the-art” steered molecular dynamics (SMD) simulations. Our SMD simulations revealed two different pathways through which a sodium ion can be expelled from the channel. Further, the SMD simulations identified the key residues that are likely to control these processes. Finally, we discuss the potential binding modes of a panel of known hNav1.5 blockers to our structural model of hNav1.5. We believe that the data presented here will enhance our understanding of the structure–property relationships of the hNav1.5 ion channel and the underlying molecular mechanisms in sodium ion permeation and drug interactions. The results presented here could be useful for designing safer drugs that do not block the hNav1.5 channel. Keywords: sodium ion channel, voltage-gated sodium channel, steered molecular dynamics, cardiotoxicity, hNav1.5, channel blockers